Day 4 Thu, May 07, 2020 2020
DOI: 10.4043/30695-ms
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Solvent Treatments for Asphaltenes on Wax Deposition and an Efficient Alternative with Green Surfactants

Abstract: Asphaltenes and waxes can precipitate and deposit in reservoirs, wells and equipment increasing production and operation costs. Previous studies showed the co-precipitation of these heavy organic compounds under field conditions and that the chemical treatment for one fraction can affect the deposition mechanism of the other fraction. These facts led to a key question: Can solvents that are normally used for asphaltenes remediations affect wax deposition? In this paper, we dealt with the impacts of aromatic so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…As a result, the density of the mixture will decrease. In this way, the mixture will begin to rise to the surface [3][4][5]. Flow assurance is risky and challenging for productive wells.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, the density of the mixture will decrease. In this way, the mixture will begin to rise to the surface [3][4][5]. Flow assurance is risky and challenging for productive wells.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanical-removal methods are the most conventional to be applied in offshore oil field development. Authors [19,20] showed that scrapers and cutters could be utilized to remove wax precipitated on tubing surfaces. Additionally, paraffin wax can be removed by scraping the tubing wall while the well is still working.…”
Section: Introductionmentioning
confidence: 99%